The chemoattractant decoy receptor D6 as a negative regulator of inflammatory responses. (25th October 2006) - Borroni, E.M.; Buracchi, C.; de la Torre, Y. Martinez; Galliera, E.; Vecchi, A.; Bonecchi, R.; Mantovani, A.; Locati, M.
Abstract : Other than signalling receptors sustaining leucocyte recruitment during inflammatory reactions, the chemokine system includes 'silent' receptors with distinct specificity and tissue distribution. The best-characterized molecule of this subgroup is the CC chemokine receptor D6, which binds most inflammatory CC chemokines and targets them to degradation via constitutive ligand-independent internalization. Structure–function analysis and recent results with gene-targeted animals indicate that D6 has unique functional and structural features, which make it ideally adapted to act as a chemokine decoy and scavenger receptor, strategically located on lymphatic endothelium and placenta to dampen inflammation in tissues and draining lymph nodes.